Comparison of the pervaporation separation of a water-acetonitrile mixture with zeolite-filled sodium alginate and poly(vinyl alcohol)-polyaniline semi-interpenetrating polymer network membranes - Naidu, B. V. K.; Bhat, S. D.; Sairam, M.; Wali, A. C.; Sawant, D. P.; Halligudi, Shivaraj B.; Mallikarjuna, N. N.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2005)
The pervaporation (PV) separation performance of ZSM-5- and Na-Y-type zeolite-filled sodium alginate (NaAlg) membranes were compared with those of pure NaAlg and semi-interpenetrating polymer network (semi-IPN) membranes of poly(vinyl alcohol) (PVA) with polyaniline (PANI) for the dehydration of acetonitrile. The PV separation characteristics of the zeolite-filled membranes showed a dependence on the nature of the zeolites. The variation of the acidity function of the ZSM-5 zeolite had an influence on the flux and selectivity of the membranes when compared to unfilled membranes. The crosslinked membranes were characterized by differential scanning calorimetry, X-ray diffraction, scanning electron microscopy, and Fourier transform infrared spectroscopy. Increasing the PANI content of the semi-IPN network increased the separation selectivity. Among the NaAlg membranes, the plain NaAlg membrane showed the highest selectivity of 414 at 30 mass % water in the feed mixture, whereas the Na-Y- and ZSM-5 (40)-filled NaAlg membranes exhibited much lower values of selectivity, that is, 7.3 and 4.3, respectively for 30 mass % water in the feed. When the flux and selectivity data of ZSM-5 (250)-filled NaAlg membranes were compared with that of Na-Y- or ZSM-5 (40)-filled NaAlg membranes, a noticeable increase in the selectivity for the ZSM-5 (250)filled NaAlg membrane was observed, but a somewhat comparable flux was observed compared to the plain NaAlg membrane. For the first time, PANI was polymerized with PVA to yield a semi-IPN. The total flux and water flux increased systematically, whereas the selectivity decreased greatly from 251.87 to 5.95 with increasing amounts of water in the feed. (c) 2005 Wiley Periodicals, Inc.
Keywords: Diffusion; interpenetrating network (IPN); zeolites

Catalytic performances of silicotungstic acid/zirconia supported SBA-15 in an esterification of benzyl alcohol with acetic acid - Sawant, Dhanashri P.; Vinu, A.; Justus, Josena; Srinivasu, P.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Liquid phase esterification of benzyl alcohol (BA) to benzyl acetate (Peach fragrance) with an acetic acid (AA) has been investigated with 12-silicotungstic acid supported on zirconia embedded inside SBA-15 (STA/ZrO2/SBA- 15) as the catalyst. Catalysts were unambiguously characterized by XRD, N-2 adsorption-desorption, FF-IR pyridine adsorption techniques and the total amount of acidity of different STA loaded catalysts was estimated by TPD of NH3. The optimization of reaction conditions of an esterification of BA with AA was performed with 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K by varying catalyst concentration (1-10 wt.% of reaction mixture); temperature, 353-383 K and AA:BA molar ratio as 0.5-3. The 15 wt.% STA/22.4 wt.% ZrO2/SBA-15 calcined at 1123 K was found to have the highest acidity and more active in the reaction. Under the optimized reaction conditions, the 15 wt.% STA/22.4 wt.%ZrO2/SBA-15 calcined at 1123 K gave 59% BA conversion with selectivity for benzyl acetate as high as 96% within 2 h of reaction time. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: 12-silicotungstic acid; Benzyl acetate; Benzyl alcohol; Esterification; SBA-15

Copper(II) ion exchanged A1SBA-15: a versatile catalyst for intermolecular hydroamination of terminal alkynes with aromatic amines - Shanbhag, Ganapati V.; Joseph, Trissa; Halligudi, Shivaraj B. (Journal of Catalysis, 2007)
The hydroarnination reaction offers a very attractive route for the synthesis of alkylated amines and their derivatives with no byproduct formation. AISBA-15 was synthesized by isomorphous substitution of aluminum into the framework of SBA-15, which induces the Bronsted acid sites, and these were exchanged with metal ions such as Cu2+, Zn2+, and Pd2+. The catalysts were characterized by XRD, N-2-sOrption, SEM, TEM, acidity measurements by FT-IR pyridine adsorption, H-2-TPR, (27)AI MAS NMR, and Si-29 MAS NMR. Hydroamination of phenylacetylene (PhAc) with 2,4-xylidine has been used as a test reaction, which gave N-(1-phenylethylidene)-2,4-dimethylaniline with no byproduct formation. CuAlSBA-15 and CuAIMCM-41 showed around three times greater activity in hydroamination of PhAc compared with Cu-clay and Cu-beta, due to the moderate Lewis acidity of Cu2+ present in mesoporous supports. The performance of the CuAlSBA-15 was also determined with different alkynes and amines to evaluate the catalyst's general applicability in hydroamination reactions. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: A1SBA-15; addition; alkyne; Amine; Copper catalyst; heterogeneous; hydroamination; ion exchange; Mesoporous

Chemoselective synthesis of beta-amino acid derivatives by hydroamination of activated olefins using AISBA-15 catalyst prepared by post-synthetic treatment - Shanbhag, Ganapati V.; Kumbar, S. M.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2008)
beta-Amino acid derivatives have a wide variety of applications viz. in the synthesis of peptide analogues, precursor for amino alcohols, optically active amino acids, lactums and diamines. Chemoselective anti-Markovnikov hydroamination reaction of activated olefins was effectively used to synthesize beta-amino acid derivatives using AlSBA-15 and AlMCM-41 catalysts. These catalysts with different Si/Al ratios were synthesized by isomorphous substitution of aluminium into the framework of SBA-15, which induces the Bronsted and Lewis acid sites. The structural integrity of the catalysts was established by characterizing with XRD, N-2-sorption, TEM, NH3-TPD Al-27 MAS NMR and Si-29 MAS NMR techniques. Hydroamination of ethyl acrylate with aniline was used as a test reaction, which gave N-[2-(ethoxycarbonyl)ethyl] aniline with high selectivity. The performance of AlSBA-15 catalyst was also determined with different acrylates and amines to know the general applicability of the catalyst in hydroamination reactions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: acrylate; activated olefin; addition; AlMCM-41; AlSBA-15; Amine; beta-amino acid; Catalyst; hydroamination; Mesoporous

Chiral Mn(III) salen complex immobilized onto ionic liquid modified mesoporous silica for oxidative kinetic resolution of secondary alcohols - Sahoo, Suman; Kumar, Pradeep; Lefebvre, F.; Halligudi, Shivaraj B. (Tetrahedron Letters, 2008)
A supported ionic liquid strategy has been applied for the immobilization of a chiral Mn(III) salen complex onto ionic liquid modified mesoporous silica SBA-15. The immobilized catalyst demonstrated high enantioselectivity and activity in the oxidative kinetic resolution of secondary alcohols, and could be recycled five times without obvious loss of activity. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Mesoporous silica SBA-15; Mn(III) salen; Oxidative kinetic resolution; Secondary alcohol; Supported ionic liquid

Comparative study on liquid phase alkylation of 2-methylnaphthalene with long chain olefins using different solid acid catalysts - Lucas, Nishita; Bordoloi, Ankur; Amrute, Amol P.; Kasinathan, Palraj; Vinu, Ajayan; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
A comparative study has been made over a variety of solid acid catalysts, which include isopoly and heteropoly ions supported on various supports such as zirconia, titania, a large variety of zeolites and a couple of mesoporous materials for liquid phasealkylation of 2-methylnaphthalene with 1-octene.All the catalyst systems were characterized by nitrogen sorption analysis, X-ray diffraction and NH(3)-TPD. Inspite of their high acid amounts zeolites gave poor catalytic performance due to their diffusional constraints; on the other hand mesoporous materials lacked diffusional constraints but due to their low acid amounts resulted in poor conversions. lsopoly and heteropoly ions supported on zirconia and titania were found to be catalytically active for the reaction due to total surface acidity. Among them, isopolytungstate supported on zirconia exhibited the best catalytic activity and was used for further optimization of reaction conditions. Excellent conversions of all olefins (>92%) with high selectivity of monoalkylmethylnaphthalene (>95%) was obtained under optimized reaction conditions. The catalyst could be recycled for several times without any obvious loss of its activity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 2-Methylnaphthalene; Alkylation; Long chain olefins; Zirconia